2022
DOI: 10.1038/s41698-022-00304-5
|View full text |Cite
|
Sign up to set email alerts
|

Secondary IDH1 resistance mutations and oncogenic IDH2 mutations cause acquired resistance to ivosidenib in cholangiocarcinoma

Abstract: The mutant IDH1 inhibitor ivosidenib improves outcomes for patients with IDH1-mutated cholangiocarcinoma, but resistance inevitably develops. Mechanisms of resistance and strategies to overcome resistance are poorly understood. Here we describe two patients with IDH1 R132C-mutated metastatic cholangiocarcinoma who developed acquired resistance to ivosidenib. After disease progression, one patient developed an oncogenic IDH2 mutation, and the second patient acquired a secondary IDH1 D279N mutation. To character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…Several clinical studies have shown that HMAs exerted better effects in AML and glioma patients with mIDHs (40)(41)(42). Considering the emergence of resistance to IDH inhibitors (43), restoring RIPK3 expression may be a potential therapeutic strategy in IDH-mutated AML. In the absence of leukemia cell lines naturally carrying mIDHs, our attempts to directly investigate that HMA-induced necroptosis and its influence on RIPK3 expression faced challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies have shown that HMAs exerted better effects in AML and glioma patients with mIDHs (40)(41)(42). Considering the emergence of resistance to IDH inhibitors (43), restoring RIPK3 expression may be a potential therapeutic strategy in IDH-mutated AML. In the absence of leukemia cell lines naturally carrying mIDHs, our attempts to directly investigate that HMA-induced necroptosis and its influence on RIPK3 expression faced challenges.…”
Section: Discussionmentioning
confidence: 99%
“…However, the study showed that the high toxicity of cabozantinib limits its use in cholangiocarcinoma patients. In addition, the use of other targeted treatments, including pemigatinib (FGFR2) and ivosidanib (IDH1), is hindered by mutation-mediated drug resistance [ 8 , 9 ]. While there is a strong need to identify more potent and specific therapeutic targets, our data support AVB-500 to control both primary and metastatic bile duct cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, another targeted therapy, ivosidanib, targeting isocitrate dehydrogenase-1 (IDH1) mutations, also showed promising results in phase III clinical trials with enhanced progression-free survival [ 7 ]. However, secondary mutations and acquired resistance to FGFR2 and IDH1 targeted therapies, along with the high toxicities observed in a phase II trial with cabozantinib, which targets VEGFR2, MET and AXL, indicate that it is crucial to identify new, specific targeted therapies that possess less normal tissue toxicity to treat bile duct cancer [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The initial results were disappointing, with the intention-to-treat analysis demonstrating significantly improved progression-free survival (PFS) in the treatment arm, but no significant difference in overall survival (OS), and an underwhelming ORR of 2.4%, representing three partial responses [ 27 ]. However, the results adjusting for crossover into the treatment arm were able to demonstrate modest improvement in OS (HR 0.49, 95% CI 0.34–0.70), as well as in PFS (HR 0.37, 95% CI 0.25–0.54) [ 28 ]. The most common treatment-related adverse event (TRAE) was ascites, seen in 11 (9%) treated patients and 4 (7%) in the placebo arm, while their quality of life appeared unchanged.…”
Section: Tumor-specific Treatmentsmentioning
confidence: 99%